Diplomatic ties between Malaysia and the Holy See: A symbol of mutual respect, inter-religious coexistence and international cooperation - Rogers, Roy Anthony (IIUM Press, 2019)
The workings within the Holy See has one of the oldest diplomatic institutions. Unlike other states with their national interests the diplomatic role of the Holy See within the international community is based on the moral authority of the Pope in favour of the wellbeing of people. Malaysia is the 179th state to have diplomatic relations with the Holy See. The relations are rather unique because no economy and consular divisions are involved. In fact, the core of the relations is based on the mutual interest of promoting justice, peace and tolerance. Although the diplomatic relations were established in 2011, this article demonstrates that there were already cordial engagements between the Popes and local leaders. This article explores the relations between Malaysia and the Holy See and analyses the reasons for Malaysia to establish relations with the Holy See and the bilateral activities. Copyright © IIUM Press